The new Oxford picture dictionary : Beginner's workbook - Zevin, Patricia E. (New York : Oxford University Press, 1989)
The New Oxford Picture Dictionary and its components provide a complete, four-skills language development program. The program is:* Practical - a wide range of topics introduce new words in their most common context.* Easy to use - vocabulary items are presented without ambiguity or the need for translation.* Versatile - the Dictionary itself and its components have unlimited applications.* Flexible - the Dictionary can be used alone or with its components.
Keywords: Picture dictionary -- English Teaching